Pengembangan Bahan Ajar Berbentuk Komik Pada Mata Peljaran IPS Materi Kelas IV SDN 1 Keruak: Development of Comic-Shaped Teaching Materials for Social Studies Subjects for Class IV SDN 1 Keruak - Ahmad Salman Alparizi (Pendidikan Al-Gafari, 2025)
Education is a planned system to create a learning atmosphere and learning or training process so that students can develop their potential. This study aims to develop and determine how students respond to comic-based teaching materials in the social studies subject matter of jobs around me in grade IV of SDN 1 Keruak. This type of research is a development using the Borg and Gall model which has been simplified into 7 stages, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, and 7) product revision. Based on the results of validation by media experts, language experts and education practitioner experts, the results of media validation with an actual score of 34 were categorized as